2004
DOI: 10.1152/ajpheart.00136.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase-2 improves cardiac function after myocardial infarction in the mouse

Abstract: Cyclooxygenase (COX)-2 is expressed in the heart in animal models of ischemic injury. Recent studies have suggested that COX-2 products are involved in inflammatory cell infiltration and fibroblast proliferation in the heart. Using a mouse model, we questioned whether 1). myocardial infarction (MI) in vivo induces COX-2 expression chronically, and 2). COX-2 inhibition reduces collagen content and improves cardiac function in mice with MI. MI was produced by ligation of the left anterior descending coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 49 publications
9
95
0
Order By: Relevance
“…6A-C) [96]. Furthermore, numerous animal studies have shown that hypertrophy and functional deterioration occur upon COX-2 overexpression, and are ameliorated by administration of COX-2 inhibitors, suggesting that COX-2 exerts cardiodepressive effects [98][99][100]. In summary, we demonstrated a negative regulation of COX-2 after ventricular unloading and suggest a central role for COX-2 in cardiomyocyte hypertrophy, since only COX-2 positive cardiomyocytes showed significant hypertrophy regression after LVAD (Fig.…”
Section: Inflammatory Factors: Cyclooxygenase-2 and Phosphorylated Aksupporting
confidence: 61%
“…6A-C) [96]. Furthermore, numerous animal studies have shown that hypertrophy and functional deterioration occur upon COX-2 overexpression, and are ameliorated by administration of COX-2 inhibitors, suggesting that COX-2 exerts cardiodepressive effects [98][99][100]. In summary, we demonstrated a negative regulation of COX-2 after ventricular unloading and suggest a central role for COX-2 in cardiomyocyte hypertrophy, since only COX-2 positive cardiomyocytes showed significant hypertrophy regression after LVAD (Fig.…”
Section: Inflammatory Factors: Cyclooxygenase-2 and Phosphorylated Aksupporting
confidence: 61%
“…We analyzed BNP and ␤-actin mRNA by real-time RT-PCR, which produced cDNAs of 241 bp (BNP) and 342 bp (␤-actin). PCR conditions and the sequences of primers and probes were reported previously (19). In brief, total RNA of NVM was extracted in Tri-Reagent (MRC) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that exogenous PGE 2 increased protein synthesis in myocytes, a marker of hypertrophic growth (26). Moreover, in a mouse model of myocardial infarction, inhibition of COX-2 decreased myocyte cross-sectional area, an index of hypertrophy (19). In addition to regulation of protein synthesis, PGE 2 also stimulated synthesis and secretion of atrial natriuretic peptide (ANP) (10) and ANP promoter activity in myocytes (27); however, no signaling mechanisms were identified in those studies.…”
mentioning
confidence: 97%
“…Quantitative real-time PCR was performed with a QuantiTect Probe PCR kit (Quiagen). 15 Fluorescence resonance energy transfer probes and primers were purchased from Applied Biosystems (Foster City, CA, USA).…”
Section: Brain Natriuretic Peptide (Bnp)mentioning
confidence: 99%